2019
DOI: 10.1080/15384101.2019.1674071
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Long non-coding RNA SNHG4 promotes cervical cancer progression through regulating c-Met via targeting miR-148a-3p

Abstract: Long non-coding RNA (lncRNA) SNHG4 has been shown to be associated with the development of a variety of cancers. The purpose of this study was to investigate the effect of SNHG4 on cervical cancer (CC) and the corresponding mechanism. The qRT-PCR was used to determine the expressions of SNHG4 and miR-148a-3p in CC cell lines and tissues. Cell apoptosis and proliferation were measured by flow cytometry and MTT assay, respectively. The interaction between SNHG4, miR-148a-3p and c-Met was verified by bioinformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“… UISS: UCLA Integrated Staging System *Each patient was staged according to 2010 AJCC TNM classification [ 18 ] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… UISS: UCLA Integrated Staging System *Each patient was staged according to 2010 AJCC TNM classification [ 18 ] …”
Section: Resultsmentioning
confidence: 99%
“…Among these SNHGs, aberrant expression of SNHG4, located in 5q31.2, has been reported in various human malignancies, such as prostate cancer, osteosarcoma, cervical cancer, and hepatocellular carcinoma [ 17 21 ]. For example, lncRNA SNHG4 facilitates cervical tumorigenesis and cancer progression by sponging miR-148a-3p and upregulating the expression of c-Met [ 18 ]. SNHG4 boosts osteosarcoma advancement by competitively binding miR-224-3p [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…miR-148a-3p has been proved to have important roles in various tumors, including esophageal squamous cell carcinoma, cervical cancer, ovarian cancer, lung cancer, and more. [33][34][35][36] Moreover, several studies have shown the potential of circulating miR-148a-3p to be a noninvasive biomarker in tumor diagnosis and surveillance. For instance, Abdollahi et al 37 identified a panel containing miR-148a-3p, which could be a diagnostic biomarker of non-small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐148a‐3p could suppress ovarian cancer progression primarily by targeting c‐Met or suppress proliferation and invasion of esophageal cancer by targeting DNMT1 20,21 . Long noncoding RNA SNHG4/miR‐148a‐3p/c‐Met axis was reported to promote cervical cancer progression 22 . In ovarian cancer, LINC00339/miR‐148a‐3p/ROCK1 axis was reported to promote cell proliferation, migration, and invasion 23 .…”
Section: Discussionmentioning
confidence: 99%